Thermodynamics of the Ca(NO3)2 – NaNO3 system. (December 2019) - Sergeev, D.; Reis, B.H.; Dreger, I.; Baben, M. to; Hack, K.; Müller, M.
Abstract: Thermodynamic properties of the quasi binary Ca(NO3 )2 –NaNO3 system are of interest with respect to thermal energy storage. In the present work the phase diagram as well as thermodynamic properties of the near eutectic mixture 45 mol% Ca(NO3 )2 – 55 mol% (NaNO3 )2 were determined experimentally and applied in the assessment of a new Gibbs energy dataset for thermochemical calculations. The enthalpy of fusion of the 45 mol% Ca(NO3 )2 – 55 mol% (NaNO3 )2 mixture is determined to be 24.7 ± 0.5 kJ/mol. The melting and crystallization enthalpy have good reproducibility, which makes it possible to use this mixture as a phase change material at temperature 225 °C. The assessed dataset describes liquid phase properties using a subregular solution model in the Redlich-Kister formalism with high accuracy. Therefore it can be used for the prediction of thermodynamic properties of different compositions in the whole Ca(NO3 )2 –NaNO3 system and be included in databases for calculation of multicomponent systems including other components.